The dragonfly pool - Ibbotson, Eva (Dutton Children's Books, 2008)
Tally and her friends at Dalderton Boarding School form a dance troupe and travel to Bergania, where she befriends Karil, the crown prince, and helps him flee the Nazis after his father is assassinated.